2020
DOI: 10.1212/wnl.0000000000010074
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte omega-3 index, ambient fine particle exposure, and brain aging

Abstract: Objective:To examine whether LCn3PUFA levels modify the potential neurotoxic effects of PM2.5 exposure on normal-appearing brain volumes among dementia-free elderly women.Methods:A total of 1,315 women (aged 65 to 80 years) free of dementia were enrolled in an observational study between 1996-9 and underwent structural brain MRI in 2005-6. Based on prospectively collected and geocoded participant addresses, we used a spatiotemporal model to estimate the 3-year average PM2.5 exposure before the MRI. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
4
19
0
Order By: Relevance
“…Fine particulate matter : Exposure to fine particle matter is thought to be a risk factor for cognitive decline [ 96 ]. A higher Omega-3 Index attenuated the inverse associations between fine particle matter exposure and white matter volumes in total brain and a number of brain areas [ 96 ].…”
Section: Brain Damagementioning
confidence: 99%
See 2 more Smart Citations
“…Fine particulate matter : Exposure to fine particle matter is thought to be a risk factor for cognitive decline [ 96 ]. A higher Omega-3 Index attenuated the inverse associations between fine particle matter exposure and white matter volumes in total brain and a number of brain areas [ 96 ].…”
Section: Brain Damagementioning
confidence: 99%
“…Fine particulate matter : Exposure to fine particle matter is thought to be a risk factor for cognitive decline [ 96 ]. A higher Omega-3 Index attenuated the inverse associations between fine particle matter exposure and white matter volumes in total brain and a number of brain areas [ 96 ]. This is probably mediated by the known anti-inflammatory effects of EPA and DHA and by their positive effects on coagulation and endothelial function [ 97 ].…”
Section: Brain Damagementioning
confidence: 99%
See 1 more Smart Citation
“…69 Imaging evidence of an association between PM2.5 exposure and neurodegenerative changes is provided by longitudinal studies of healthy patients with interval MRI scans, which have shown white matter loss in those exposed to greater concentrations of PM2.5. [70][71][72][73][74] PM(coarse) has been less well-studied and only a single report linking exposure in women to decreased mini-mental status examination (MMSE) score has been published. 75 Exposure to PM10, particularly in patients harboring the APOE4 allele, has been shown to associate both with dementia incidence and rate of cognitive decline, as well as front-temporal thinning on MRI.…”
Section: Dementiamentioning
confidence: 99%
“…2001 ), flavonoids ( Shishtar et al. 2020 ), and long-chain omega-3 polyunsaturated fatty acids (LCn3PUFAs) ( Chen et al. 2020 ; McNamara et al.…”
Section: Introductionmentioning
confidence: 99%